Correlation between C-Reactive Protein in Peripheral Vein and Coronary Sinus in Stable and Unstable Angina - Leite,Weverton Ferreira (2015)
Background: High sensitivity C-reactive protein (hs-CRP) is commonly used in clinical practice to assess cardiovascular risk. However, a correlation has not yet been established between the absolute levels of peripheral and central hs-CRP. Objective: To assess the correlation between serum hs-CRP levels (mg/L) in a peripheral vein in the left forearm (LFPV) with those in the coronary sinus (CS) of patients with coronary artery disease (CAD) and a diagnosis of stable angina (SA) or unstable angina (UA). Methods: This observational, descriptive, and cross-sectional study was conducted at the Instituto do Coração, Hospital das Clinicas, Faculdade de Medicina, Universidade de São Paulo, and at the Hospital Beneficência Portuguesa de Sao Paulo, where CAD patients referred to the hospital for coronary angiography were evaluated. Results: Forty patients with CAD (20 with SA and 20 with UA) were included in the study. Blood samples from LFPV and CS were collected before coronary angiography. Furthermore, analysis of the correlation between serum levels of hs-CRP in LFPV versus CS showed a strong linear correlation for both SA (r = 0.993, p < 0.001) and UA (r = 0.976, p < 0.001) and for the entire sample (r = 0.985, p < 0.001). Conclusion: Our data suggest a strong linear correlation between hs-CRP levels in LFPV versus CS in patients with SA and UA.